Environmental factors affecting pondweeds in water bodies of northwest Poland - Merdalski, Marek; Banaś, Krzysztof; Ronowski, Rafał (Biodiversity: Research and Conservation, 2019)
There was a statistically significant difference (p<0.001) between the environmental factors affecting Potamogeton and Stuckenia, respectively, within each of the waterbody types studied. In lakes, Potamogeton occupied poorer habitats than Stuckenia, with lower conductivity, redox, PAR intensity, concentration of bicarbonates, calcium and chlorides and lower calcium content in the sediment. In watercourses, Potamogeton occurred in less coloured and less oxygenated waters than Stuckenia, but richer in CO2 and chlorides, better insolated and flowing faster. It also occupied less alkaline sediment, but of higher conductivity. In estuaries, Potamogeton occurred in waters with a relatively low concentration of chlorides and calcium than Stuckenia, lower pH and conductivity, but more coloured and, consequently, with lower PAR. C&RT analysis showed mineral concentration (Ca2+, Cl−, HCO3−) in the water, its conductivity, colour and flow to be the highest-ranking environmental factors affecting pondweeds.